Design sistêmico e ecoinovação em APLs: o método F.L.O.R.A como estratégia sustentável aplicada para o polo de confecções de Pernambuco - Oliveira, Emilio Augusto Gomes de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This research work relates the areas of ecology and design to a convergent situations on the contemporary paradigm of sustainability. These are two areas that have in common, a systemic view of the processes and mechanisms of operation, whereas, ecology studies the relationships ecosystem of nature and, in turn, the design, the interdisciplinary processes and iterative methodology for artifacts development. Therefore, as a reference guidelines for building human communities and production processes more sustainable, this paper point that can be used the following ecosystem principles ecosystem: interdependence, feedback, cooperation, differentiation, adaptation and optimization. The utilization of the systemic thinking and functioning analogous to nature allows a direction to the construction and consolidation of a new paradigm of innovation, which contributes to a saving light for this scenario demanded by sustainability, not only this generation, but also to future. At the same time, this new economy is also based on the improvement of social welfare, while significantly reduces environmental risks and ecological scarcity of resources. In this scenario there is growing number of companies and organizations offering specialized services to promote actions for sustainability indicator by increasing management and reactive, proactive and ecoinnovative policies mainly through design strategies. Specifically, in this research, the emphasis of the work of the designer, as a manager, applies to the textile and clothing sector. Thus, the central aim of this qualitative research is to present a method of eco-innovation through design systemic, as a sustainable strategy to be applied for the cluster hub of Pernambuco. Hereinafter called F.L.O.R.A., its operations involves five systemic actions, associated with ecological principles that were cited. Based on these, and seamlessly, designers can therefore refer to any proposals for eco-innovation...

A presente pequisa relaciona as áreas da ecologia e do design, de maneira convergente, diante do paradigma contemporâneo da sustentabilidade. Trata-se de duas áreas que têm em comum a visão sistêmica dos processos e mecanismos de funcionamento, ou seja, na ecologia, estuda-se as relações ecossistêmicas da natureza e, por sua vez, no design, os processos interdisciplinares e metodologia iterativa no desenvolvimento de artefatos. Portanto, como referência para diretrizes de construção de comunidades e processos de produção mais sustentáveis, podem ser utilizadas os seguintes princípios ecossistêmicos, apontados neste trabalho: interdependência, feedbacks, cooperação diferenciação, adaptação e otimização. O uso do pensamento sistêmico e análogo ao funcionamento da natureza possibilita uma direção à construção e consolidação de um novo paradigma de inovação, o qual contribui para uma economia leve para este cenário demandado pela sustentabilidade, não apenas a esta geração, mas também às futuras. Ao mesmo tempo, esta nova economia também se baseia na melhoria do bem-estar social, ao passo que reduz, significativamente, os riscos ambientais e a escassez de recursos ecológicos. Neste cenário há um número crescente de organizações oferecendo serviços especializados em promover ações indicadores de sustentabilidade pelo incremento de gestão e políticas ambientais reativas e principalmente ecoinovadoras, através de estratégias de design. Especificamente, neste trabalho, a ênfase da atuação do designer, enquanto gestor, se aplica ao segmento têxtil e de confecções. Sendo assim, o objetivo central desta pesquisa qualitativa é apresentar um método de ecoinovação, por meio do design sistêmico, como estratégia sustentável aplicada para a APL do Polo de Confecções de PE. Doravante denominado F.L.O.R.A., seu operacionamento envolve cinco ações sistêmicas, associadas aos princípios...
Keywords: Desenho industrial; Desenvolvimento sustentável; Vestuario - Indústria - Pernambuco; Ecologia; Industrial design